Different fasting periods in tiletamine-zolezepam-anethetized cats: Glycemia, recovery, blood-gas and cardiorrespiratory parameters - Gering, Ana Paula [UNESP]; Nunes, Newton [UNESP]; Oliveira, Michele C. C. [UNESP]; Horr, Monica [UNESP]; Lopes, Patricia Cristina Ferro [UNESP]; Tormena, Analia Angelica (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2013)
The effects of different fasting periods on glycemia levels and on cardiorrespiratory parameters in tiletamine-zolazepam-anesthetized cats were evaluated. Twenty one animals were randomly assigned to three groups: 8 hours (G8), 12 hours (G12) or 18 hours (G18) of the preoperative fasting. The tiletamine-zolazepam (2 mg/kg) was administered intravenously. The heart rate (HR), respiratory rate (fR), rectal temperature (TR), glycemia (G), laboratorial glycemia (Glab), venous oxygen partial pressure (PvO2), venous carbon dioxide partial pressure (PvCO2), venous hemoglobin saturation (SvO2), pH, base deficit (BD), bicarbonate concentration (HCO3-) and haematocrit were evaluated at 90 minutes after the last meal (T0), immediately before anesthesia (T1) and at ten (T2) and thirty (T3) minutes after tiletamine-zolezepam administration. The time between the administration of anesthetic and the cat's trial to elevate head (Th) and the interval between drug administration and aniamal's quadrupedal position (Tqp) were recorded. No differences among groups were recorded for glycemia, HR, PvO2, SvO2, pH, BD, HCO3-, Ht and Tqp. In G12 from T2, glycemia increased and from T1 PvCO2 decreased. At T1, PvO2 increased in all groups. In G8 and G12, from T1, DB and HCO3- decreased. In G12 and G18, from T2, Ht decreased. In G12, the Th mean was higher than G8. In conclusion, in tiletamine-zolazepam-anesthetized cats, the different preoperative fasting did not influence glycemia, blood-gas and cardiorrespiratory parameters. Additionally, there was no relationship between glycemia and anesthesia recovery.
Keywords: Cats; Dissociative anesthesia; Glycemia; Monitoring; Recovery